2020
DOI: 10.1177/2473011420908841
|View full text |Cite
|
Sign up to set email alerts
|

Primary Arthrodesis for Diabetic Ankle Fractures

Abstract: Background: Treatment of ankle fractures in patients with diabetes is associated with increased complication rates. Ankle arthrodesis is considered a salvage procedure after failed ankle fracture fixation, yet primary ankle arthrodesis has been proposed as a treatment option for patients with significant diabetes-related complications. To date, the characteristics of patients who undergo primary ankle arthrodesis and the associated outcomes have not been described. Methods: A retrospective review was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Ankle arthrodesis is considered a salvage operation for failed as well as neglected ankle fracture [21,22]. Classic indications of ankle fusion in ankle fractures are diabetics with uncontrolled diabetes with a high risk of developing charcot arthropathy as well as patients with neglected fractures of the ankle with non-reconstructable malleoli or malunited ankle fractures in low-demand individuals as well as in patients with failed internal fixation of ankle fractures [23][24][25]. The authors expanded on these indications and performed ankle fusion in patients who presented late (over 12 weeks) or had undergone failed ankle fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Ankle arthrodesis is considered a salvage operation for failed as well as neglected ankle fracture [21,22]. Classic indications of ankle fusion in ankle fractures are diabetics with uncontrolled diabetes with a high risk of developing charcot arthropathy as well as patients with neglected fractures of the ankle with non-reconstructable malleoli or malunited ankle fractures in low-demand individuals as well as in patients with failed internal fixation of ankle fractures [23][24][25]. The authors expanded on these indications and performed ankle fusion in patients who presented late (over 12 weeks) or had undergone failed ankle fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Grote et al retrospectively reviewed 13 patients with diabetes who underwent primary TTC arthrodesis for unstable ankle fractures with formal preparation of the tibiotalar joint (Level IV evidence) 66 . They noted a high overall complication rate with 10/13 (76.9%) of experiencing at least 1 complication and 5/13 (38.5%) requiring operative debridement for infection.…”
Section: Operative Techniques and Considerationsmentioning
confidence: 99%
“…Grote et al 49 reported a case series of 13 diabetic patients with unstable ankle fractures that underwent primary arthrodesis of the tibiotalar joint. Eighty-two percent of the patients had peripheral neuropathy.…”
Section: Arthrodesismentioning
confidence: 99%